Monographs of rural communities: Polish school of research - Bukraba-Rylska, Barbara (Eastern European Countryside, 2024)
This article presents the most important dilemmas related to the monographic method, discussing them on the example of monographs of Polish villages. Particular emphasis is put on contentious issues such as: research statics – dynamics, representativeness – generalisations, and enumerative induction – analytic induction. The analysis of the selected monographs reveals that most of the objections reported with respect to such publications (i.e. focus on describing rather than analysing the problem, providing unnecessary details, lack of representativeness, and insufficient theoretical reflection) seem to be unfounded. In the end the article discusses circumstances that point to the need to return to this method, particularly in countries peripheral to the centre of the global academic field.